Semen inflammatory markers and Chlamydia trachomatis infection in male partners of infertile couples. (9th December 2015) - Dehghan Marvast, L.; Aflatoonian, A.; Talebi, A. R.; Ghasemzadeh, J.; Pacey, A. A.
Summary: Previous studies have given conflicting results about the effect of generally infection and Chlamydia trachomatis on seminal ILs and semen parameters. The aim of this study was to investigate the relationship between semen quality and the level of seminal interleukins (ILs) in infertile couples with C. trachomatis . Blood, first void urine (FVU) and semen were obtained from 250 infertile men who had failed to conceive after 12 months of trying. Serological analysis for specific IgA, IgM and IgG antibodies to C. trachomatis in serum, the presence of C. trachomatis in FVU and semen sample and semen analysis were carried out. The main results are as follows: (i) elevated IL‐6 and IL‐8 are observed in C. trachomatis ‐positive men, but this is not significant and it varies by diagnostic method; and (ii) IL‐6 and IL‐8 levels were correlated with each other and the concentration of leucocytes, but IL‐8 was correlated with semen volume and patient's age. This study showed that men with such an infection in FVU samples (PCR positive) had only lower semen volume compared with men without infection.